Principals' Intellectual Stimulation Strategies and Teachers' Job Satisfaction in Public Secondary Schools in Ilorin East, Nigeria - Ajape, Rasheedat Oladunni; Ayuba, Abdulrazaq Olayiwola (Chalim Journal of Teaching and Learning, 2024)
This study investigates the relationship between principals' intellectual stimulation strategies and teachers' job satisfaction in public secondary schools in Ilorin East, Nigeria. The research addresses three primary questions and one hypothesis regarding the impact of leadership strategies on teacher satisfaction. A total of 323 questionnaires were distributed to teachers but 212 completed responses were suitable for analysis. The findings revealed a significant positive correlation (r = 0.696, p < 0.05) between principals' intellectual stimulation strategies and teachers' job satisfaction. Specifically, strategies such as fostering professional development, encouraging collaboration, and promoting innovative teaching practices were positively associated with higher levels of job satisfaction among teachers. The results underscore the importance of transformational leadership in enhancing teacher morale and engagement. In conclusion, the study highlights that effective intellectual stimulation practices implemented by school principals significantly contribute to improving teachers' job satisfaction. It was recommended that professional development programs should be established to equip principals with the skills necessary to foster such an environment, ultimately benefiting both educators and students in the Nigerian educational landscape.